Eptifibatide use in ischemic stroke patients undergoing endovascular thrombectomy: A matched cohort analysis - Rana, Ameena; Yu, Siyuan; Reid-Herrera, Savina; Kamen, Scott; Hunter, Krystal; Shaikh, Hamza; Jovin, Tudor; Thon, Olga R.; Patel, Parth; Siegler, James E.; Thon, Jesse M. (Frontiers in Neurology, 2022)
Introduction Small studies have suggested that eptifibatide (EPT) may be safe in acute ischemic stroke (AIS) following intravenous thrombolysis or during endovascular therapy (EVT) for large vessel occlusion (LVO). However, studies are called upon to better delineate the safety of EPT use during EVT. Methods A comprehensive stroke center registry (09/2015-12/2020) of consecutive adults who had undergone EVT for anterior LVO was queried. Patients treated with EPT were matched with 2 control groups based on known factors associated with intracranial hemorrhage (ICH) risk - age, Alberta Stroke Program Early Computed Tomography Score (ASPECTS), and number of thrombectomy passes. Safety outcomes (intracranial hemorrhage [ICH], parenchymal hematoma [PH-2] grade hemorrhagic transformation, symptomatic ICH [sICH]) and efficacy outcomes (TICI 2B/3 recanalization, 24-h National Institutes of Health Stroke Scale [NIHSS] score), were compared between matched groups using descriptive statistics. In addition, multivariable logistic regression was used to assess for an association between EPT and PH-1/PH-2 grade hemorrhages. Results A total of 162 patients were included, 54 of whom (33%) received EPT. The rate of ICH was similar between groups (p = 0.62), while PH-2 was significantly more frequent with EPT (16.7% EPT vs. 3.7 vs. 1.9%; p = 0.009), but without significant differences in sICH (5.6% EPT vs. 7.4 vs. 3.7%; p = 0.72). Rates of TICI Score ≥ 2B were nominally higher with EPT use (83.3 vs. 77.8 vs. 77.8%, p = 0.70). Between the EPT and control groups, there were no differences in 24-h NIHSS (p = 0.09) or 90-day mortality (p = 0.58). Our adjusted multivariate analysis identified that the number of passes (p < 0.01), EPT use (p < 0.01), and tandem occlusion (p = 0.03) were independent predictors of PH1/PH2 grade hemorrhage. Additionally, every unit increase in number of passes resulted in a 1.5 times greater odds of a high-grade hemorrhagic transformation in EPT-treated patients (adjusted OR = 1.594). Conclusion In this single-center analysis, EPT use during EVT was associated with a significantly higher rate of PH1/PH2 grade hemorrhages, but not with differences in sICH, 24-h NIHSS, or 90-day mortality. Randomized prospective trials are needed to determine the safety and efficacy of EPT in this population.